Six thinking hats - De Bono, Edward (Australia : Penguin Books, 2008)
"Thinking often proceeds as drift and waffle and reaction," writes de Bono. In this book, he presents a way to become a better thinker. He separates thinking into six distinct modes, identified with six colored "thinking hats": White: facts, figures, and objective information; Red: emotions and feelings; Black: logical negative thoughts; Yellow: positive constructive thoughts; Green: creativity and new ideas; and Blue: control of the other hats and thinking steps. "Putting on" a hat focuses thinking; "switching" hats redirects thinking. With the different parts of the thinking process defined, discussions can be better focused and more productive. Using real-life situations as examples, de Bono creates scenarios that show how the effective use of "thinking hats" can: focus thinking more clearly; lead to more creative thinking; and improve communication and thus decision-making.
Keywords: Thought and thinking; Creativity; Thinking